Phenotypic variation in morphological traits, fruit, seed and oil of jathropa (Jathropa curcas) from three provenance - Vallesteros, Shierel F.; Carandang, Wilfredo M.; Vallesteros, Arvin P. (2011)
Jathropa (Jathropa curcas L.) is a promising crop for large-scale production of biodiesel. In recent years, it has become a focus of research and development investments in many relevant government agencies and private companies in the Philippines. Heightened attention to jathropa was driven by the belief that it can be made to yield the desired quantity of product in marginal lands; and growing it in marginal lands would prevent the food and fuel competition. Widely distributed across the country, identification of provenances that will give higher seed yield and oil content is deemed necessary before large plantations are established. Eight trees from each of the three provenances planted in Mt. Makiling in Los Baños, Laguna were selected from among the experimental plants to examine tree-to-tree variation. The provenances were Bacolod, South Cotabato, and Talisay. Variability was large in all morphological traits, the highest being in length of unbranched stem (CV=46.51%) and number of first order branches (CV=33.72%). Seed yield was positively and significantly correlated with basal diameter, length of unbranched stem, and crown diameter. Variability was small in fruit and seed traits. Crown diameter appeared to be a predictor (P<0.05) of three seed size parameters, namely; length, breadth and thickness. Among the seed traits, seed length was significantly correlated (r=0.498) with oil content. The oil content in kernel ranged from 41.40% to 59.26%.
Keywords: Jatropha; Seeds; Fruits; Oil